A Supported Nickel Phthalocyanine Complex as a Selective Catalyst for the Production of Styrene - Salah A. Hassan; Afaf A. Zahran; Fatma Z. Yehia (Adsorption Science & Technology)
A nickel phthalocyanine complex (NiPc) supported on bentonite clay (Bihar, India) was used as a selective catalyst for the dehydrogenation of ethylbenzene to styrene. Maximum activity was observed for the catalyst sample containing 1.0 wt% NiPc/bentonite. A higher loading of complex (> 1.4 wt%) exhibited no activity and resembled polycrystalline NiPc. The texture of the studied catalyst and the mode of surface dispersion of the supported NiPc were investigated through the adsorption of N 2 and O 2 , respectively. The activity of the diluted samples could be attributed to the presence of separate highly dispersed molecules of NiPc on the bentonite surface without having a marked effect on its pore system for most active samples. The selectivity towards styrene was found to depend strongly on the NiPc surface area and the degree of dispersion. The activity was a function of the whole structure including modifications of both acid sites through different interactions and of the pore system through a penetration mechanism.